2017
DOI: 10.18632/oncotarget.22290
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin attenuates locomotor and cognitive deficits as well as hippocampal neuronal injury through the PI3K/Akt1/GSK-3β signaling pathway in an in vivo model of cerebral ischemia

Abstract: Ischemic stroke causes irreversible damage to the brain. The hippocampus is a vulnerable region and plays an important role in cognition and locomotor activity. Puerarin is a phytoestrogen that has beneficial effects in treating neurological disorders. How puerarin protects against hippocampal injury and its molecular mechanisms remain to be elucidated. Transient global brain ischemia was induced by 4-vessel occlusion in adult male Sprague-Dawley rats. The rats were pretreated with puerarin alone or together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 46 publications
(58 reference statements)
2
38
0
Order By: Relevance
“…Once the events that led to hippocampal damage had already initiated, we speculate that a higher dose of coumestrol would be necessary. In previous reports on experimental global cerebral ischemia, a single dose of coumestrol or other phytoestrogens were administered pre‐ or post‐insult, was able to protect the vulnerable hippocampal CA1 and to prevent cell death, thus significantly reducing the lesion volume (Canal Castro et al, 2012; Tao et al, 2017; Wang et al, 2013). Based in our data, it can be suggested that the beneficial effects of coumestrol are determined by mitigating the late tissue loss and late astrocytic activation in ipsilesional hippocampus after HI insult.…”
Section: Discussionmentioning
confidence: 98%
“…Once the events that led to hippocampal damage had already initiated, we speculate that a higher dose of coumestrol would be necessary. In previous reports on experimental global cerebral ischemia, a single dose of coumestrol or other phytoestrogens were administered pre‐ or post‐insult, was able to protect the vulnerable hippocampal CA1 and to prevent cell death, thus significantly reducing the lesion volume (Canal Castro et al, 2012; Tao et al, 2017; Wang et al, 2013). Based in our data, it can be suggested that the beneficial effects of coumestrol are determined by mitigating the late tissue loss and late astrocytic activation in ipsilesional hippocampus after HI insult.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the ERK1/2-Runx2 signaling pathway was engaged in the mechanism of PUR in promoting osteogenic differentiation [28]. PUR could attenuate hippocampal neuronal injury through the PI3K/Akt1/GSK-3β signaling pathway [29]. In our previous studies, the PI3K/Akt signaling pathway was found to be significantly activated in the protective effect of icariin on human NPCs [30] in unfavorable inflammatory microenvironment.…”
Section: Introductionmentioning
confidence: 94%
“…Stem Cells International antiapoptosis agent, which can also activate the PI3K/Akt pathway [51]. Specifically, PUR could attenuate cognitive deficits by increasing survival hippocampal CA1 pyramidal neurons [29] and remit daunorubicin-induced apoptosis of H9c2 cells [51] through Akt phosphorylation. Similarly, based on our findings, the PI3K/Akt pathway was inhibited in human NPMSCs under compression, and PUR treatment could reactivate the pathway.…”
mentioning
confidence: 99%
“…The Morris maze test is a well-proven method for evaluating place navigation and spatial ability to assess spatial reference memory in rodents. The procedure is divided into two phases: place navigation and spatial probe 20 . In the place navigation trial, rats were trained to find the escape platform.…”
Section: Effects Of Extract Of C Japonica On Impairment Of Rat Placementioning
confidence: 99%